What Motivates People to Pay for Online Sports Streaming? An Empirical Evaluation of the Revised Technology Acceptance Model - Sun, Ye; Zhang, Huifeng (Frontiers in Psychology, 2021)
With the rapid development of Internet technology, sports media consumption is migrating towards streaming. The online streaming of sporting events has become the important way of copyrights holders to engage sports fans, especially young fans. Therefore, it is vital to understanding users’ willingness to pay (WTP). Given that previous studies of the livestream sports broadcasts online have not dealt with users’ payment intention, the originality of this study is that it explore users’ motivation by combining information system research with the consumer demand theory. The study aimed to examine the factors that influence users’ payment intention to stream online sports by using the extended Technology Acceptance Model (TAM). Data from questionnaires completed by 330 Chinese respondents determined how perceived usefulness, ease, enjoyment, and satisfaction, influence users’ WTP. Satisfaction positively correlated with users’ payment intentions, impacted WTP values, mediated ease of use. The analysis also revealed the necessity for broadcast platforms to improve satisfaction and to increase payment intentions.